Climatic influence on children’s atopic skin studied by changes in skin hydration - a pilot study. - Martinsen, Ø.G.; Grimnes, S.; Aas, K. (European Journal of Pediatric Dermatology, 2007)
We have studied the effect of a four-week stay on a sunny, seaside resort on children's atopic dermatitis, assessed by means of changes in skin hydration level. The skin hydration was determined using low frequency electrical susceptance measurements. Skin hydration was found to drop significantly during the first two weeks, followed by a significant increase in hydration again during the next two weeks. We interpret this as being due to two different mechanisms that result from the treatment and healing of the skin. First there will be a decrease in skin hydration due to the restoration of the barrier function of the skin because of the curative effect of the climate and possibly the treatment with skin moisturisers. Secondly, the direct effects of e.g. the seawater and skin moisturisers will lead to an increase in the hydration of the stratum corneum.